Aripiprazole Selectively Reduces Motor Tics in a Young Animal Model for Tourette’s Syndrome and Comorbid Attention Deficit and Hyperactivity Disorder - Rizzo, Francesca; Nespoli, Ester; Abaei, Alireza; Bar-Gad, Izhar; Deelchand, Dinesh K.; Fegert, Jörg; Rasche, Volker; Hengerer, Bastian; Boeckers, Tobias M. (Frontiers in Neurology, 2018)
Tourette’s syndrome (TS) is a neurodevelopmental disorder characterized primarily by motor and vocal tics. Comorbidities such as attention deficit and hyperactivity disorder (ADHD) are observed in over 50% of TS patients. We applied aripiprazole in a juvenile rat model that displays motor tics and hyperactivity. We additionally assessed the amount of ultrasonic vocalizations (USvs) as an indicator for the presence of vocal tics and evaluated the changes in the striatal neurometabolism using in vivo proton magnetic resonance spectroscopy (1H-MRS) at 11.7T. Thirty-one juvenile spontaneously hypertensive rats (SHR) underwent bicuculline striatal microinjection and treatment with either aripiprazole or vehicle. Control groups were sham operated and sham injected. Behavior, ultrasonic vocalizations (USVs) and striatal neurochemical profile were analyzed at early, middle and late adolescence (postnatal day 35 to 50). Bicuculline microinjections in the dorsolateral striatum induced motor tics in SHR juvenile rats. Acute aripiprazole administration selectively reduced both tic frequency and latency; whereas stereotypies, USVs and hyperactivity remained unaltered. The striatal neurochemical profile was only moderately altered after tic-induction and was not affected by systemic drug treatment. When applied to a young rat model that provides high degrees of construct, face and predictive validity for TS and comorbid ADHD, aripiprazole selectively reduces motor tics, revealing that tics and stereotypies are distinct phenomena in line with clinical treatment of patients. Finally, our 1H-MRS results, suggest a critical revision of the striatal role in the hypothesized cortico-striatal dysregulation in TS pathophysiology.